Peran Pelaksana Sekolah Penggerak dalam Transformasi Pendidikan Berkualitas yang Berkelanjutan - Rachman, Fazli; Yunita, Sri; Junaidi, Junaidi; Giri, Taufiq Wijaya; Ramadhani, Agung Pratama; Simarmata, Yemima Putri Bona; Purba, Anjeli Harpina; Amelia, Icha (Jurnal Kewarganegaraan, 2024)
AbstractThis research is interesting because it aims to photograph the efforts of educational units implementing the mobilization school program to achieve program objectives. The review was carried out on the conceptual research gap, namely the citizenship behavior of program implementers in their educational unit organizations. This qualitative research was carried out with a descriptive design. The research was conducted at SMAS An-Nizam Medan because it had been designated as a driving school, with a technique for determining respondents using purposive sampling. Data was analyzed using an interactive model. Efforts to transform education through driving schools at SMAS AN-Nizam Medan to create conditions and work environments that support: first, the implementation of the Pancasila student profile. Second, improving and equalizing the quality of driving school administrators. Third, create a collaborative climate between the driving school organizing elements in the school. The driving school organizing element is reflected in the school's elements to show concern and commitment in working highly dedicated to the transformation of education in schools. This reflection is a picture of the citizen good of an educational unit and the organizational citizenship behavior at SMAS AN-Nizam Medan.------------------AbstrakPenelitian ini menarik karena bertujuan untuk memotret upaya satuan pendidikan pelaksana program sekolah penggerak untuk mencapai tujuan program. Tinjauan dilakukan pada konseptual gap penelitian yaitu perilaku kewarganegaraan pelaksana program dalam organisasi satuan pendidikannya. Penelitian kualitatif ini dilakukan desain deskriptif. Penelitian dilakukan di SMAS An-Nizam Medan karena telah ditetapkan sebagai sekolah penggerak, dengan teknik penentuan responden menggunakan purposive sampling. Data dianalisis menggunakan model interaktif. Upaya transformasi pendidikan melalui sekolah penggerak di SMAS AN-Nizam Medan untuk menciptakan kondisi dan lingkungan kerja yang mendukung: pertama, implementasi profil pelajar Pancasila. Kedua, peningkatan dan pemerataan kualitas penyelenggara sekolah penggerak. Ketiga, menciptakan iklim kolaboratif antar unsur penyelenggara sekolah penggerak di sekolah. Unsur penyelenggara sekolah menggerak tercermin dari unsur-unsur sekolah untuk menunjukkan kepedulian dan komitmen dalam bekerja yang berdedikasi tinggi untuk transformasi pendidikan di sekolah. Cerminan tersebut merupakan gambaran dari œwarga satuan pendidikan yang baik dan perilaku kewarganegaraan organisasi di SMAS AN-Nizam Medan.